Factors Affecting Graduate Competence in Independent Learning Policies Independent Campus - Tuti Hermelinda; Upi Niarti; Silvia Syeptiani (Journal of Vocational Education Studies, 2022)
Learning in the Merdeka Campus provides challenges and opportunities for the development of innovation, creativity, capacity, personality, and student needs, as well as developing independence in seeking and finding knowledge through realities and field dynamics such as ability requirements, real problems, social interaction, collaboration, self-management, performance demands, targets and achievements. Through an independent learning program that is well designed and implemented, students' hard and soft skills will be formed strongly.The tight competition in the world of work entering the industrial era requires university graduates to compete by equipping themselves with various skills. The competence of college graduates is one of the determining factors to be able to compete in the world of work. Higher education graduates are mainly required to be up to date with the development of science and technology so that they can become graduates who are ready to use and are competitive. It is undeniable, with the advancement of science and technology, the roles and functions of humans have begun to be replaced by information technology that was created to simplify and accelerate human work. This study aims to analyze the factors that influence the competence of college graduates, namely emotional intelligence, learning behavior and academic achievement. Graduate competence refers to the Graduate Competency Standards according to the National Higher Education Standards, namely Attitudes, Knowledge and Skills. The scope of the research is final semester students at the Raflesia Polytechnic with 120 respondents. Data collection techniques using a Likert scale 1-5 questionnaire. The analysis used statistical tests, namely the F test and t test with the help of SPSS. The results showed that simultaneously emotional intelligence, learning behavior and academic achievement had a significant effect on graduate competence, while partially emotional intelligence and academic achievement had a significant effect on graduate competence